DINAMIKA OTONOMI DAERAH DALAM PENGEMBANGAN METODE PARTISIPASI PUBLIK PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN (2) - R. Herlambang Perdana Wiratraman (Universitas Airlangga, 2010)
This article is taken from the research to study local democracy dynamic in regional autonomy transition, especially after the enactment of Law No. 32 of 2004 concerning on Regional Government and Law No 10 of 2004 concerning on Legislation Making. These laws have influenced the process of public policy making at field. This research analyse the implementation the word ’berhak’ (right to) as stipulated under article 53 of Law No. 10 of 2004. From this point of view, this continues by mapping the development strategy in making legislation at regional level, mainly by searching to what extend public participation processes would contribute at that level. In local political context, the research aims to study how political participation at local level fully involves citizen to take decision, especially connected to: First, economic democracy which is a participatory magement all citizen in productive assets and collective property rights. Second, politic pluralism democracy which is an understanding and sensitivity over pluralistic and locality aspects of the needs and aspirations any citizen in public policy making. The research method uses a non-doctrinal legal research, especially by emplying sociology of law and political economy of law. The result is written in descriptive-analytic model. The research only limits on the development of public participatory method, so then it would have critical points in reforming law and institution, especially to guarantee public participation rights. The recommendations are: First, the needs of key action and more participative for reforming all policies at regional level, by emphasizing through (1) state institution reconstruction which more guarantees citizen political participation; (2) the shifting from ‘top-down’ to ‘bottom up’ processes; (3) the empowerment of people (capacity building) and local institutional strengthening. Second, strengthening legal framework for public participation, either at legislation or regulation levels. The public participation initiative through regional regulation or to improve parliament mechanism order are important to develop public participation methods in local regulation making. Furthermore, The research needs to be followed up by studying deeply about how the legal framework to secure better should be formulated, especialy in responding public participation, either better procedural control or substantial control from public. This research contributes partly in providing possible models and [legal] formulations which are more responsive to the people needs and justice, also to strengthen democratization processes in local governance system.Keywords : Public Participations, Local Autonomy, Local Regulations